2005
DOI: 10.5194/acp-5-3423-2005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the uptake of N<sub>2</sub>O<sub>5</sub> on mineral dust at 298 K

Abstract: Abstract. The heterogeneous reaction of N 2 O 5 with mineral (Saharan) dust has been studied at T=298 K using a combination of Knudsen and DRIFTS cells for kinetic and product investigations, respectively. The initial uptake coefficient has been determined to be γ =(8.0±0.3)·10 −2 . This uptake slowly saturates into a steady state uptake of γ =(1.3±0.3)·10 −2 suggesting that reaction of N 2 O 5 with the mineral dust surface and hydrolysis of N 2 O 5 on the surface take place simultaneously. Both uptake coeffic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 37 publications
7
78
0
Order By: Relevance
“…The kinetics of the uptake of N 2 O 5 onto desert dust particles and their surrogates (e.g., Arizona Test Dust, illite) has been reported by several previous studies (Karagulian et al, 2006;Mogili et al, 2006;Seisel et al, 2005;Tang et al, 2010Tang et al, , 2012Tang et al, , 2014Wagner et al, 2008Wagner et al, , 2009). In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The kinetics of the uptake of N 2 O 5 onto desert dust particles and their surrogates (e.g., Arizona Test Dust, illite) has been reported by several previous studies (Karagulian et al, 2006;Mogili et al, 2006;Seisel et al, 2005;Tang et al, 2010Tang et al, , 2012Tang et al, , 2014Wagner et al, 2008Wagner et al, , 2009). In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible.…”
Section: Introductionmentioning
confidence: 58%
“…In addition, Seisel et al (2005) observed the formation of nitrate on mineral dust particles due to the uptake of N 2 O 5 using diffuse reflectance FTIR (Fourier transform infrared spectroscopy), and Tang et al (2012) further confirmed that the yield of nitrate is ∼ 2 (as expected from Reaction R1) within the experimental uncertainty, and that the formation of NO 2 is negligible. However, to the best of our knowledge, the reaction of N 2 O 5 with TiO 2 has never been studied.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…14,16 A similar phenomenon was also observed for the uptake of HNO 3 on soot 47 and N 2 O 5 and H 2 O on mineral dust. 48,49 This implies a very small probe depth or a large true uptake coefficient of amines on citric acid. On the other hand, as discussed above, the reaction degree is lower than 0.05% even for the whole exposure time for all of these amines on citric acid.…”
Section: −1mentioning
confidence: 99%